Using traffic simulation to quantify performance improvement due to vehicular traffic reduction at a university campus. (7th May 2020) - Hamad, Khaled
The purpose of this study is to quantify the benefits of reducing vehicular traffic at a university campus resulting from adopting sustainable transport modes to travel to campus. To this end, a traffic simulation model was developed to estimate improvements in several traffic and environmental performance measures. A total of 11 traffic scenarios were simulated and their results were compared. These scenarios varied from a baseline situation, i.e., the current AM peak-hour traffic, to a variety of traffic-reduction scenarios ranging from 5% to 50% with an increment of 5%. The results showed considerable improvements in traffic flow and air-pollution performance measures. All performance measures witnessed steady improvement as more traffic reduction occurred; nevertheless, traffic measures have seen more improvement as opposed to environmental measures. Statistical significance tests showed that 5% traffic reductions did not show significant impacts on performance, 10% reductions will improve traffic flow, whereas 20% traffic reductions will improve both traffic and air emissions.